INTERPRETASI SUFISTIK ATAS HADIS MELALUI SASTRA DALAM SYAIR PERAHU KARYA HAMZAH FANSURI - M. Ahsin; M. Alfatih Suryadilaga (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
The understanding of hadith is so far still dominated by hadith scholars with various methodologies and approaches that have been standardized in conducting studies on the hadith. Understanding of hadith is not only performed by hadith scholars but also by Sufism scholars. One of the applications in understanding hadith by Sufism scholars is done through poetry media. One of the figures included in this category is Hamzah Fansuri that can be seen from his works, One of which is the "Syair Perahu" (the boat poem). Syair Perahu loads hadith contents such as faith, knowledge, preparing charity towards the afterlife, Barzakh eschatology, and tawhid values. Syair Perahu is full of signs used as symbols in conveying prophetic messages, such as boats, merchants, sea, islands, and so on. To find the content of the meaning contained in the Syair Perahu, the writer will apply Charles S. Peirce's semiotic theory. The results of this study found that literature, in this case Syair Perahu, became a medium to convey meaning understood by interpretant. This study also found the tendency of the Sufis represented by Hamzah Fansuri towards hadiths that have eschatological nuances. Hamzah Fansuri's understanding of the hadith in the Syair Perahu rejected the assumption of some people that his Sufism understanding deviated from correct understanding. Through the study of semiotics, Hamzah Fanzuri used the type of icon and index signs by using ligisign representamen, which indicated that he maintains the principles of meaning by paying attention to signs close to the intended meaning in the text of the hadith.